MODELING THE CHARACTERISTICS OF A BROADBAND ANTENNA SYSTEM FOR UAV DIRECTION FINDING - BOIKO, Juliy; POLIKAROVSKYKH, Oleksiy; TKACHUK, Vitaliy; AVDIEIEV, Victor; SVISTUNOV, Oleksiy (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of the development and modelling of a broadband antenna system for Unmanned Aerial Vehicle (UAV) direction finding. The research covered the issues of analytical description of the antenna system based on the prototype - the Vivaldi antennas. The article presents a mathematical description of the Vivaldi antenna element model. An experimental relationship between the geometrical parameters and characteristics of the antenna has been established. A review of the current state of the issue of designing antenna systems based on the concept of building ultra-wideband directional antenna elements in the absence of a phase centre has been carried out. The main trends in the modern design of broadband antenna systems are determined. The main parameters of the proposed broadband antenna are determined by the method of mathematical modelling. The parameters of the proposed antenna in the frequency range under various excitation conditions are studied, and the specifics of the application of such a system under the conditions of its possible use as part of UAV direction-finding complexes are given. The most optimal design option for an ultra-wideband antenna element is a design with an expanding slot (similar to Vivaldi antennas). At present, these antennas are widely used in various devices, namely, in radio reconnaissance devices, medical equipment, etc. Their popularity is due to the presence of advantages over other antennas, among which are a wide operating frequency range, simple design, simple manufacturing requirements, and high gain. In this paper, we considered Tapered Slot Antenna - an antenna with a widening slot. The antenna element designed and modelled in the article is a modified Vivaldi antenna (an antenna with a quasi-slot line with expansion), which is being developed for the direction-finding complex of the UAV. When calculating the TSA of the antenna element, the program for calculating the characteristics of the antennas MMANA was used in order to accelerate the study of the main laws for obtaining the required characteristics. Particular attention was paid to the possibility of changing the radiation pattern (RP) depending on the phase relations of the voltage at the input of the antenna elements.
Keywords: UAV; antenna; direction finding; radiation pattern; broadband antenna emitter